LEAVES AREA OF SPRING WHEAT PLANTS DEPENDING ON PRESEEDING TREATMENT OF SEEDS AND VARIETIES - Balykin Alexey Anatolyevich; Shashkarov Leonid Gennadievich; Mefodyev Georgiy Anatolyevich; Semenov Vladimir Grigoryevich (Scientific Journal of Pedagogy and Economics, 2020)
The article deals with the formation of the area of leaves of spring wheat depending on the treatment of seeds and varieties in the conditions of the Chuvash Republic. Three varieties of Margarita, Simbircite, and Prokhorovka were studied. The second factor is seed treatment in three gradations: 1. Without processing (control). 2. Seed treatment with the drug Benlate. 3. Seed treatment with Nano-Gro. The results of the analysis of leaves area formation are presented. Determining the optimal leaves area is a very complex problem. Solar radiation at an insufficient leaves area of field plants is absorbed not completely; at the greatest developed leaf surface the same phenomenon occurs. In combination with the seed protectant of spring grain crops – Benlate, the authors also studied the effect of Nano-Gro. The presowing treatment of seeds with the Nano-Gro solution significantly affects the increase in the formation of the leaves area of spring wheat.